(untitled) (Research, Society and Development, 2021)
Entrepreneurial behavior in employees (intrapreneurship) is increasingly becoming a differential for dynamic development in organizations. The presence of social sustainability within organizations, whether in its promotion or application, combined with individualist and self-centered intrapreneurial behavior, causes losses, disaffections and incompatibility with the purposes of companies inherent to the objectives of sustainable development. The present study aims to analyze, discuss and propose a model for identifying the behavior of the self-centered intrapreneur, as well as a model for the identification and maintenance of the eco-intrapreneur collaborator (eco-intrapreneur) in Brazilian organizations from the perspective of individual resignification. . As for the methodological procedures, the research is bibliographic and descriptive with a qualitative approach. Preliminarily with respect to the results of this study, it appears that the self-centeredness of the intrapreneur leads to negative results. However, through the model of identification and maintenance of the eco-intrapreneurial employee that resignifies organizational demands, it is possible for the organization to anticipate itself, avoiding negative results and adapting strategies.